Mobile, Phased-Array, Doppler Radar Observations of Tornadoes at X Band - (:unkn) unknown (My University, 2012)
Previous studies of tornadoes have utilized high-spatial-resolution data obtained by mobile Doppler radars to better understand phenomena that occur on small spatial scales. There has not been a similar focus on using high-temporal-resolution radar data to investigate short-time-scale volumetric processes that occur in tornadoes. The Mobile Weather Radar, 2005 X-band, Phased-Array (MWR-05XP) is a hybrid phased-array Doppler radar that obtains volumetric data of weather phenomena in ~10 seconds, an order of magnitude faster than that of other mobile Doppler radars. Data obtained by the MWR-05XP from 2008-2010 are used to examine (i) short-time-scale processes that occur in tornadoes, and (ii) the volumetric evolution of tornadoes in supercells.

Tornadic supercell datasets from three dates are studied in-depth to learn more about the tornadogenesis process and volumetric characteristics of tornadoes. It is found that tornadic vortex signatures (TVSs) form upward with time at tornadogenesis for two cases. These results are consistent with mobile, Doppler radar observations of tornadogenesis from the past ~10 years, but counter to studies prior to that, in which a descending TVS was observed in roughly half of tornado cases utilizing WSR-88D data. Possible explanations for this apparent discrepancy in the literature are discussed using a comparative example. Also, it is found that tornadoes can undergo short-time-scale fluctuations in intensity likely not the result of multiple vortices. These fluctuations are shown to have strong height dependence. In one case, the intensity fluctuations are strong enough that the TVS aloft cannot be detected for a short time before it strengthens again. The lack of TVS detection at certain times may be evidence of height-dependent tornado decay and subsequent secondary genesis.

Finally, volumetric characteristics of TVSs up through storm midlevels are discussed. Vertical Delta-V profiles and tornado orientation are examined during multiple phases of tornado lifecycles to determine their general trends in time and whether they hold promise in the future as real-time predictors of tornado behavior. TVS vertical Delta-V profiles are found to have a distinct signal during the dissipation phases of two tornadoes, though TVS tilt is found to be highly variable at all times. The volumetric evolution of tornado dissipation also is studied. TVSs are found to dissipate first at 2-3 km and then quickly upward and slowly downward from there. Concurrently, TVSs are observed to move in radically different directions at different height levels. Possible explanations for disparate tornado motion and the resulting dissipation are provided.
Keywords: Doppler radar; Tornadoes; Radar meteorology